ANALISIS ASPEK KELISANAN PADA HIKAYAT PERANG PANDAWA JAYA - Sheila Amalia Mustofa; Asep Yudha Wirajaya (Universitas Nasional, 2021)
The manuscript studied in this study is the story of the Hikayat Perang Pandawa Jaya. This manuscript is themed on one of the great epics of India, namely Mahabharata. In this study, philological work steps are used to explain the description of the manuscript. In addition, this study will also present an analysis of oral aspects according to Walter J. Ong. Oral aspect analysis is used to determine the oral elements contained in the story of the Hikayat Perang Pandawa Jaya. The results of the analysis show that the Hikayat Perang Pandawa Jaya contains several oral aspects expressed by Walter J. Ong. These include additive, aggregative, close to everyday life, conservative, participatory, and homocentric. The steps of philological work are appropriate when used to study the Hikayat Perang Pandawa Jaya which is a type of old Malay manuscript.